THE DEVELOPMENT OF MAKAN SIRIH DANCE AS A MALAY IDENTITY IN PEKANBARU CITY (1957-2009): Perkembangan Tari Makan Sirih Sebagai Identitas Melayu di Kota Pekanbaru (1957-2009) - Bunari; Yuliantoro; Ulya Tania Kusumawati Ulyatania (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to examine the development of the Makan Sirih Dance in shaping and representing the cultural identity of the Malay community in Pekanbaru City. This dance was first created by O.K. Nizami Jamil at the beginning of the formation of Riau Province as a performance to welcome honored guests in official state events. Over time, the Makan Sirih Dance has undergone a shift in function, from being formal to becoming part of the customary procession in Malay weddings. This study uses historical research methods consisting of four stages: heuristics, source criticism, interpretation, and historiography. Data sources are obtained through literature studies, archives, documentation, and interviews. The research results show that the Makan Sirih Dance has developed not only as a form of performing art but also as a symbol of respect, acceptance, and the identity of the Malay community in Pekanbaru. Its existence until 2009 reflects the strong efforts to preserve culture amidst the ongoing social dynamics.